Effect of mastectomy on gut microbiota and its metabolites in patients with breast cancer - Fan, Pingming; Ding, Linwei; Du, Guankui; Wei, Changyuan (Frontiers in Microbiology, 2024)
The relationship between gut microbiota and breast cancer has been extensively studied, however changes in gut microbiota after breast cancer surgery are still largely unknown.The patient underwent routine open surgery for breast cancer at the First Affiliated Hospital of Hainan Medical College from 2022.6.1 to 2022.12.1. Stool samples were collected from the patients preoperatively, 3 and 7 days postoperatively. Stool samples were subjected to 16s rRNA sequencing.Results: Surgery did not affect the α-diversity of gut microbiota. The β-diversity and composition of gut microorganisms was significantly affected by surgery in breast cancer patients. Both Lefse analysis and between-group differences analysis showed that surgery led to a decrease in the abundance of the Firmicutes and Lachnospiraceae, and an increase in the abundance of Proteobacteria and Enterobacteriaceae. Moreover, 127 differential metabolites were screened and classified into 5 categories based on their changing trends. KEGG enrichment analysis showed significant changes in phenylalanine metabolic pathway and exogenous substance metabolic pathway. Eight characterized metabolites were screened by ROC analysis.Our study found that breast cancer surgery significantly altered gut microbiota composition and metabolites, with decreases in beneficial bacteria and increases in potentially harmful bacteria. This underscores the importance of enhanced postoperative management to optimize gut microbiota.